Who owns that song?: The Battle for Subramania Bharati s Copyright - A.R. Venkatachalapathy (Juggernaut Books, 2018)
A contemporary of Rabindranath Tagore and one of the greatest Tamil poets of all time, Subramania Bharati belongs to the legion of artists whose works remain unrecognized during their lifetime but go on to gain enormous fame. In 1921, when Bharati died in poverty, his unlettered young widow, Chellamma, sold his works to his stepbrother. But in the wake of the freedom struggle, along with the music boom launched by gramophone records and the rise of the talkies, Bharati s songs became commercially valuable. A powerful movie mogul, A.V. Meiyappan of AVM studios, bought the rights to Bharati s works and when someone else used a Bharati song in his film, AVM sued him. A controversy followed, and for the first time in the history of literature there was a popular agitation demanding the nationalization of a writer s work. The newly independent state could ill afford to let an iconic poet s writings be private property. After a series of legal wrangles, the poet s writings were nationalized and put into the public domain in 1949. In Who Owns That Song? A.R. Venkatachalapathy tells the fascinating story of this unique and dramatic episode through the lives of the various colourful characters involved, drawing on a variety of historical sources, and tackling its most challenging question: who does an artist belong to?